Geological map of Peru - Instituto Geológico Minero y Metalúrgico. Dirección de Geología Regional (2022)
The Geological map represents the types of rock, soils and geological structures of the national territory, which includes the seabed. INGEMMET makes available this version of the Geological Map of Peru at a scale of 1:1,000,000, and updates the second version published in 1999. This version was also elaborated based on the 501 quadrangles of the National Geological Chart. In addition, the geological mapping of the checked and updated quadrangles between 2000 and 2003, which belong to the second edition of the National Geological Chart at a scale of 1: 100,000 and 1: 50,000, was integrated. The topographic base was provided by the National Geographic Institute (IGN) and the departmental limits by the National Institute of Statistics and Information (INEI). The map coordinate system of the geological is GCS (Geographic Coordinate System), WGS84 (Word Geodetic System).